2010
DOI: 10.1002/adma.201003129
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Durable Superhydrophobic Surfaces

Abstract: Development of durable non-wetting surfaces is hindered by the fragility of the microscopic roughness features that are necessary for superhydrophobicity. Mechanical wear on superhydrophobic surfaces usually shows as increased sticking of water, leading to loss of non-wettability. Increased wear resistance has been demonstrated by exploiting hierarchical roughness where nanoscale roughness is protected to some degree by large scale features, and avoiding the use of hydrophilic bulk materials is shown to help p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
760
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 997 publications
(766 citation statements)
references
References 48 publications
5
760
0
1
Order By: Relevance
“…Relatively poor or reduced performance was reported for several types of SHSs tested under repeated icing/deicing conditions [15,16,22,29,31], which was attributed to their poor abrasive resistance (also reported by others in a concise review [32]). In parallel, SHSs were reported to lose their anti-icing performance in a humid atmosphere, when icing follows (or occurs simultaneously with) water condensation or frost formation in their rough structures [2,13,16,22,33].…”
mentioning
confidence: 67%
“…Relatively poor or reduced performance was reported for several types of SHSs tested under repeated icing/deicing conditions [15,16,22,29,31], which was attributed to their poor abrasive resistance (also reported by others in a concise review [32]). In parallel, SHSs were reported to lose their anti-icing performance in a humid atmosphere, when icing follows (or occurs simultaneously with) water condensation or frost formation in their rough structures [2,13,16,22,33].…”
mentioning
confidence: 67%
“…Moreover, surface defects and surface inhomogeneity are challenging to probe by using any of the conventional methods. Thus, new approaches are needed for studying directly the energy dissipation in dynamic moving droplets under well-defined lateral and normal forces, in order to understand energy dissipation, defects and wear on the intrinsically fragile superhydrophobic surfaces 32 .…”
mentioning
confidence: 99%
“…Compared with many years of development on durability of superhydrophobic surfaces, 124 the research on superoleophobic surfaces has just begun. Wang et al reported a superoleophobic rough alumina surface with selfhealing property, which showed good durability to external mechanical damage.…”
Section: Transparencymentioning
confidence: 99%